DEVELOPMENT OF GRAMMAR SKILLS OF HIGH SCHOOL STUDENTS BASED ON MULTIMEDIA PROGRAMS (USING ENGLISH AS AN EXAMPLE) - G.Sharipova, (TADQIQOTLAR, 2026)
Abstract This article discusses the importance of multimedia technologies in developing English grammar skills among high school students. Modern educational technologies create interactive learning environments that increase learners’ motivation and improve grammatical competence. The paper analyzes the effectiveness of multimedia tools such  as  videos,  animations,  online  exercises,  and  educational  platforms  in  English language teaching. The study also highlights innovative teaching methods that help students understand and apply grammar rules more effectively.